Dietary and circulating butyrate are independently associated with kidney function in diabetes: a dual-cohort analysis - Zhao, Leying; Zhao, Cong; Li, Aoshuang; Gao, Qinyang; Ai, Sinan; Wang, Yaoxian; Chen, Zhenjie; Wang, Zhen (Frontiers in Nutrition, 2025)
BackgroundThe gut microbiota-derived metabolite butyrate has been implicated in maintaining renal homeostasis through anti-inflammatory and immunomodulatory pathways. However, evidence from large-scale human studies, especially in high-risk diabetic populations, remains limited. This study aimed to investigate the association between butyrate exposure and renal function in adults with diabetes, using a dual-cohort design.MethodsWe analyzed data from 7,723 adults with diabetes across ten NHANES cycles (1999–2018) to evaluate the association of dietary butyrate intake with estimated glomerular filtration rate (eGFR) and albuminuria. Multivariable linear regression, restricted cubic spline modeling, and subgroup analyses were performed with survey weighting. For external validation, we recruited a Chinese cohort of 70 patients with diabetic kidney disease (DKD) and measured serum butyrate and isobutyrate concentrations using UPLC-MS/MS. Associations with eGFR and 24-h urinary protein were assessed using adjusted regression models.ResultsIn the NHANES cohort, higher dietary butyrate intake was independently associated with a higher eGFR (β = 1.61; 95% CI: 0.29–2.92; p = 0.02), with a significant nonlinear dose–response (P for non-linearity = 0.0006). No significant associations were found with albuminuria. In the Chinese cohort, serum butyrate was positively associated with eGFR (β = 0.05; 95% CI: 0.01–0.08; p = 0.02), but not with proteinuria. Serum isobutyrate also showed a positive association with eGFR (β = 0.15; 95% CI: 0.02–0.28; p = 0.02). Sensitivity analyses confirmed the robustness of these findings among participants with both diabetes and CKD.ConclusionThis dual-cohort study provides the first epidemiological evidence that higher levels of butyrate—whether from dietary intake or serum concentration—are independently associated with better renal function in adults with diabetes. These findings underscore the relevance of the gut-kidney axis in diabetic kidney disease and suggest that enhancing endogenous butyrate production through diet or microbiota-targeted strategies may offer a novel avenue for renoprotection.